Hybrid Securities and the Debt-Equity Classification Problem - Geronimo, Russell Stanley Q. (2019)
The debt-equity classification problem appears at first glance to be a simple matter until one deals with: (i) hybrid securities with characteristics of both debt and equity, and (ii) aggressive financial engineering and tax planning techniques that exploit the differential regulatory treatment between debt and equity instruments, an activity called "regulatory arbitrage". This paper provides a systematic method of dealing with the debt-equity classification problem, with focus on corporate taxation. In achieving this, this paper: (i) surveys hybrid securities in the Philippine capital markets; (ii) describes their role in regulatory arbitrage; (iii) surveys rules on debt-equity distinction formulated by judges; (iv) proposes a general principle underlying the debt-equity distinction based on the concept of the equity-holder as "bearer of the residual risk"; and (v) develops a tool for classifying hybrid securities through a scoring system which ranks these securities based on their proximity to debt or equity. This paper will then apply this tool in developing a debt-equity continuum that visually illustrates which Philippine hybrid security has predominant debt or equity features. In doing this, this paper can assist practitioners manage legal risks arising from, as well as assist judges and regulators in deciding disputes about, the debt-equity classification problem.
Keywords: Commercial law; Commercial loans; Hybrid securities; Debt equity conversion